Type and abundance of Gastropods in Mangrove Area in Rawa Mekar Jaya Village Sungai Apit Sub-district Siak Regency Riau Province - Sri Ika Wulandary; Eni Sumiarsih; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on July 2019 in the mangrove forest Rawa Mekar Jaya Village, Sungai Apit Sub-district, Siak Regency, Riau Province. This research aims to determine the type and abundance of gastropods in Rawa Mekar Jaya Village. The sampling method using a fixed transect lines combined with 1x1 quadrant (m²). Gastropods found were 4 species: Telescopium telescopium, Ellobium aurisjudae, Cerithidea quadrata, and Neritina violacea. Results shown that the highest species abundance obtained from Cerithidea quadrata with 35.334 ind/ha and the lowest was Ellobium aurisjudae with 19.668 ind/ha . The highest gastropod abundance was found in Station III with 144.000 ind/ha, while the lowest gastropod abundance was found in Station I with 71.333 ind/ha. Keywords :Gastropods, abundance, line transect mangrove, Siak Regency